Addressing gender-based violence and harassment in a work health and safety framework - Rachel Cox (International Labour Organization (ILO), 2024)
This report looks at the implications of addressing gender-based violence and harassment (GBVH) under a work health and safety (WHS) framework. It describes the characteristics of gender-responsive WHS approaches to prevention of violence and harassment, in particular with respect to risk assessment and other WHS prevention mechanisms. Integration of rights and obligations under equality and non-discrimination legislation and WHS legislation are considered, specifically with respect to responses to GBVH within organizations and access to remedies for workers who have been harmed by such behaviour. Parallel prevention duties incumbent on organizations are also considered. The report concludes that addressing GBVH under a WHS framework allows for proactive, systematic, collective, inclusive and publicly enforceable approaches to prevention. As such, WHS regimes have the potential to offer the kind of progressive and transformational change needed to prevent GBVH at work and ensure that women's and other people's equality rights, as well as their health and safety, are respected. However, given historical and ongoing resistance to the idea that GBVH is a work-related risk, a legal obligation to conduct a gender-responsive risk assessment emerges as an important precondition for effective prevention.
Keywords: 330